1994
DOI: 10.1002/bdd.2510150609
|View full text |Cite
|
Sign up to set email alerts
|

The influence of food on the disposition of the antiepileptic oxcarbazepine and its major metabolites in healthy volunteers

Abstract: The effect of food on the pharmacokinetics of the antiepileptic oxcarbazepine (OXC) was investigated in healthy volunteers. Six healthy male volunteers were treated with single peroral doses of 600 mg of oxcarbazepine (Trileptal) after overnight fasting or a fat- and protein-rich breakfast. Mean (+/- SD) areas under the plasma concentration-time curves (AUC) of the major component in plasma, the active monohydroxy metabolite (MHD), which is responsible for the therapeutic effect in man, were 672 (25) mumol L-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 7 publications
0
10
0
1
Order By: Relevance
“…It had been reported that the systemic bioavailability of MHD was increased by approximately 17% when oxcarbazepine was taken with food. 59,60 However, with a newer oxcarbazepine formulation, there was no effect of food on the bioavailability of MHD (data on file, Novartis Pharmaceuticals Corp.). Peak plasma concentrations of MHD occurred 4-6 hours after a single dose of either oxcarbazepine 400 mg or oxcarbazepine 600 mg. 57,61 The plasma terminal half-life of oxcarbazepine was between 1 and 2.5 hours, 62 whereas the plasma MHD terminal halflife averaged 9.3 ± 1.8 hours after administration of a single dose.…”
Section: Clinical Pharmacokineticsmentioning
confidence: 99%
“…It had been reported that the systemic bioavailability of MHD was increased by approximately 17% when oxcarbazepine was taken with food. 59,60 However, with a newer oxcarbazepine formulation, there was no effect of food on the bioavailability of MHD (data on file, Novartis Pharmaceuticals Corp.). Peak plasma concentrations of MHD occurred 4-6 hours after a single dose of either oxcarbazepine 400 mg or oxcarbazepine 600 mg. 57,61 The plasma terminal half-life of oxcarbazepine was between 1 and 2.5 hours, 62 whereas the plasma MHD terminal halflife averaged 9.3 ± 1.8 hours after administration of a single dose.…”
Section: Clinical Pharmacokineticsmentioning
confidence: 99%
“…The 2 formulations manifested equivalent therapeutic efficacy.b) 10 healthy volunteers,b) Chronopharmacokinetics of PHT2. No evidence that circadian rhythms influenced absorption and distribution.Degen et al, 1994 [112]6 healthy volunteersEffect of food on pharmacokinetics of OXC1. AUC: increased by 16 % and Cmax increased by 23 % when OXC was given with food.2.…”
Section: Chronopharmacodynamics Of Epilepsy Medicationsmentioning
confidence: 99%
“…41, Suppl. 8,2000 a complex combination of drug interactions may lead to serious adverse events. It is possible that other such interactions occur that have not yet been elucidated.…”
Section: Hepatic Inductionmentioning
confidence: 99%